I am so sorry this is the wrong answer
Step-by-step explanation:
with your square root symbol I never know what is inside the square root and what is possibly outside.
so, I can only guess and see what comes close.
f(x) = 2x² + x - 1
g(x) = sqrt(2x - 1) ??? is that so ?
h(x) = -2
2g(f(x)) + h(x)
g(f(x)) means that the whole f(x) expression is used as x in g(x).
the whole combined function is then
2×sqrt(2(2x² + x - 1) - 1) - 2
2×sqrt(4x² + 2x - 2 - 1) - 2
2×sqrt(4x² + 2x - 3) - 2
and if I am not mistaken, then this is the solution you mentioned at the beginning (if I try to read between the typos and missing info).
this is how people get to this.
do you understand it now ? or is there still something unclear ?
Answer:
0.5
Step-by-step explanation:
sjsbdir rievrjrvrjrbrhdbdjdbekebejebsjsbsirvrirvrjrrhirvrjrbrjr dry it said it had to be 20 characters long
Answer:
16 responses
Step-by-step explanation:
we know that
A geometric sequence, is a sequence of numbers where each term after the first is found by multiplying the previous one by a fixed, non-zero number called the common ratio.
![a_n=r^{n-1}](https://tex.z-dn.net/?f=a_n%3Dr%5E%7Bn-1%7D)
where
a_n---->
term of the sequence
r ---> is the common ratio
a ---> the first term of the sequence
![a=50\\r=100\%-10\%=90\%=90/100=0.90](https://tex.z-dn.net/?f=a%3D50%5C%5Cr%3D100%5C%25-10%5C%25%3D90%5C%25%3D90%2F100%3D0.90)
substitute
![a_n=50(0.90)^{n-1}](https://tex.z-dn.net/?f=a_n%3D50%280.90%29%5E%7Bn-1%7D)
For n=12
substitute
![a_n=50(0.90)^{12-1}=16](https://tex.z-dn.net/?f=a_n%3D50%280.90%29%5E%7B12-1%7D%3D16)
Answer:
The equation of line with given points is y - 4 = 3 ( x + 2 ) .
Step-by-step explanation:
Given as :
The points of line are ( 1 , 13 ) and ( - 2 , 4 )
The point slope intercept equation of line is
y -
= m ( x -
)
Where m is the slope of line
So , Slope , m = ![\frac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D)
Or, m = ![\frac{4 - 13}{ - 2 - 1}](https://tex.z-dn.net/?f=%5Cfrac%7B4%20-%2013%7D%7B%20-%202%20-%201%7D)
Or, m = ![\frac{ - 9}{ - 3}](https://tex.z-dn.net/?f=%5Cfrac%7B%20-%209%7D%7B%20-%203%7D)
∴ m = 3
Now The equation of line is
y -
= m ( x -
)
Or. y - 13 = 3 ( x - 1 )
Or, y - 13 = 3 x - 3
Or, y = 3 x - 3 + 13
∴ y = 3 x + 10
I.e y - 4 = 3 x + 6
Or, y - 4 = 3 ( x + 2 )
Hence The equation of line with given points is y - 4 = 3 ( x + 2 ) . Answer